2018
DOI: 10.1002/jcp.27207
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed Th17/Treg balance, cytokines, and miRNAs in peripheral blood of patients with Behcet’s disease

Abstract: Impaired inflammatory immune cells have been implicated in the pathogenesis ofBehcet's disease (BD). In the current study, we aimed to evaluate the frequency of T helper (Th) 17 and regulatory T (Treg) cells, cytokine secretion, the expression of transcription factors related to Th17 and Treg cells, and microRNAs (miRNAs) targeting these transcription factors in BD patients. Blood samples from 47 BD patients and 58 healthy subjects were drawn, and the peripheral blood mononuclear cells (PBMCs) were separated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 49 publications
3
39
0
Order By: Relevance
“…Several studies of BD have demonstrated that a significant increase of serum IL-17 is an indicator of reactive or recurrence of infection [25, 26]. To determine whether CD83 siRNA could improve the symptoms of BD by downregulating IL-17, plasma IL-17 levels were measured in CD83 siRNA-treated BD mice by ELISA.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies of BD have demonstrated that a significant increase of serum IL-17 is an indicator of reactive or recurrence of infection [25, 26]. To determine whether CD83 siRNA could improve the symptoms of BD by downregulating IL-17, plasma IL-17 levels were measured in CD83 siRNA-treated BD mice by ELISA.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, disclosing the mechanisms that control the balance between Treg/Th17 cells is a critical factor in pathogenesis, prognosis and therapy of several immune-related disorders. [110][111][112] Likewise, a large number of studies have reported that miRNAs play a pivotal role in regulating the mTOR signaling pathway and fine-tuning the development of both Tregs and Th17 cells. A forward genetic screen for identifying miRNAs involved in the regulation of Treg cell differentiation revealed that out of 130 candidates, 29 miRNAs had a negative effect and 10 had a positive effect.…”
Section: Mirnas Control the Balance Between Th17 And Tregs By Regulating The Expression Of Mtormentioning
confidence: 99%
“…Th‐17 cells are a relatively new subset of T helper cells mainly producing IL‐17A, IL‐17F, IL‐22 and TNF‐α (Annunziato, Cosmi, Liotta, Maggi, & Romagnani, ). Recent data have proven the involvement of IL‐17 and Th17 cell responses in the pathogenesis of Behcet's disease and shown the Behcet activated by high serum levels of interleukins 6, 10 17, 23, as well as Th17 cells (Abolhasani, Gholizadeh Ghaleh Aziz, Khabbazi, & Alipour, ; Ahmadi et al, ; Alipour, Nouri, et al, ; Alipour, Sakhinia, et al, ; Chi et al, ). Therapeutic methods such as interferon alfa and anti‐TNF‐α (Tumour necrosis Factor alpha) agents that are effective in Behcet's disease with eye contamination have revealed that they inhibit responses of Th17 cell (Liu, Yang, Wang, Li, & Kijlstra, ; Sugita et al, ).…”
Section: Introductionmentioning
confidence: 99%